Optimization of a Natural-Deep-Eutectic-Solvent-Based Dispersive Liquid–Liquid Microextraction Method for the Multi-Target Determination of Emerging Contaminants in Wastewater - Beatriz Gómez-Nieto; Antigoni Konomi; Georgios Gkotsis; Maria-Christina Nika; Nikolaos S. Thomaidis (Molecules)
The widespread discharge of industrial and urban waste has led to significant increases in the environmental concentrations of numerous chemical substances. This work presents the development of a simple and environmentally friendly dispersive liquid–liquid microextraction (DLLME) method based on a hydrophobic natural deep eutectic solvent (NADES) for the determination of selected compounds from benzotriazole, benzothiazole, paraben, and UV filter families in wastewater samples. Of the twelve NADES formulations evaluated, those composed of a 4:1 molar ratio of thymol and menthol presented the highest extraction efficiencies. The influence of key experimental variables such as the pH of the aqueous sample, the ratio of NADES phase to sample volume, and the extraction time on the extraction efficiency was investigated using a multivariate optimization. Under optimal conditions, relative standard deviations below 15% and recoveries for spiked wastewater samples ranged between 82 and 108%, demonstrating the suitability of the method for routine water-quality monitoring. The sustainability and practicality of the developed method was evaluated using the assessment tools ChlorTox, AGREEprep, AGRRE, and BAGI, obtaining scores of 0.005 g in the NADES-DLLME method, 0.70, 0.52, and 72.5, respectively, demonstrating that the method is green and reliable.